FAM20C could be targeted by TET1 to promote odontoblastic differentiation potential of human dental pulp cells. (25th December 2017) - Li, Qimeng; Yi, Baicheng; Feng, Zhihui; Meng, Runsha; Tian, Cheng; Xu, Qiong
Abstract: Objectives: Ten‐eleven translocation 1 (TET1) is a DNA methylcytosine (mC) dioxygenase discovered recently that can convert 5‐mC into 5‐hydroxymethylcytosine (5hmC). We previously reported that TET1 promotes odontoblastic differentiation of human dental pulp cells (hDPCs). The gene encoding the family with sequence similarity 20, member C (FAM20C) protein, is a potential TET1 target and showed demethylation during odontoblastic differentiation of hDPCs in our previous study. This study aimed to explore whether TET1‐mediated hydroxymethylation could activate the FAM20C gene, thereby regulating hDPC differentiation. Materials and methods: The expression pattern of FAM20C and its potential changes during odontoblastic induction of hDPCs were assessed by Western blotting. Lentivirus‐mediated transduction with short hairpin RNA (shRNA) was used to knock down FAM20C and TET1 expression in hDPCs. The mineralization potential of hDPCs was evaluated with an ALPase activity assay and by observing the mineralized matrix deposition and the expression of odontoblast‐related markers DSPP and DMP1. Recombinant human FAM20C protein (rhFAM20C) was reintroduced into shTET1 cells in a rescue experiment. The dynamic hydroxymethylation status of the FAM20C gene promoter was examined using hydroxymethylated DNA immunoprecipitation (IP)‐PCR. Chromatin IP‐PCR and agarose gel electrophoresis were utilized to validate the recruitment of TET1 to its target loci in the FAM20C promoter. Results: FAM20C protein level was upregulated after the odontoblastic induction of hDPCs. shRNA‐mediated FAM20C suppression reduced the expression of DSPP and DMP1 after odontoblastic induction for 7 and 14 days. ALPase activity was reduced on day 7, and the formation of mineralized nodules was attenuated on day 14 after odontoblastic induction in FAM20C‐inhibited hDPCs. Genomic 5hmC levels significantly decreased, and total 5mC levels increased in TET1‐deficient hDPCs. In addition, a significant reduction in FAM20C also emerged. The rhFAM20C treatment of shTET1 cells attenuated the mineralization abnormalities caused by TET1 depletion. TET1 depletion prompted a decline in 5hmC levels in several regions on the FAM20C promoter. Enhanced TET1 recruitment was detected at the corresponding loci in the FAM20C promoter during odontoblastic induction. Conclusion: TET1 knockdown suppressed odontoblastic differentiation by restraining its direct binding to FAM20C promoter, and hence inhibiting FAM20C hydroxymethylation and subsequent transcription. These results suggest that TET1 potentially promotes the cytodifferentiation potential of hDPCs through its DNA demethylation machinery and upregulation of FAM20C protein expression.